Recent advances in innovative biomaterials for promoting bladder regeneration: processing and functionalization - Zhang, Yi; Ding, Fu’an; Han, Junjie; Wang, Zongliang; Tian, Wenjie (Frontiers in Bioengineering and Biotechnology, 2025)
The bladder is a dynamic organ located in the lower urinary tract, responsible for complex and important physiological activities in the human body, including collecting and storing urine. Severe diseases or bladder injuries often lead to tissue destruction and loss of normal function, requiring surgical intervention and reconstruction. The rapid development of innovative biomaterials has brought revolutionary opportunities for modern urology to overcome the limitations of tissue transplantation. This article first summarized the latest research progress in the processing approaches and functionalization of acellular matrix, hydrogels, nanomaterials, and porous scaffolds in repairing and reconstructing the physiological structure and dynamic function of damaged bladder. Then, we discussed emerging strategies for bladder regeneration and functional recovery, such as cell therapy, organoids, etc. Finally, we outlined the important issues and future development prospects of biomaterials in bladder regeneration to inspire future research directions. By reviewing these innovative biomaterials and technologies, we hope to provide appropriate insights to achieve the ultimate goal of designing and manufacturing artificial bladder substitutes with ideal performance in all aspects.